Kuching gets rights to host IAC2020 - Amalia, Madihie (New Sarawak Tribune, 2016)
An announcement to host the IAC2020 conference in Kuching was made at the International Seminar on Professional Counselling (International ProCoun'16) on 12th October 2016.